PRIMARY OUTCOME MEASURES IN PEDIATRIC SEPTIC SHOCK TRIALS : A SYSTEMATIC REVIEW - Al Ansoriani, Marogi; Rahayu Kosasih, Dina Mentayani; Alam Al Ansoriani, Nuansa Nur (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Septic is a significant global health concern for children, with about 1.2 million cases each year and varying mortality rates up to 50%. Clinical research in pediatric septic shock faces challenges in choosing appropriate outcome measures beyond mortality due to diverse mortality rates and patient populations. As a result, there's a need for comprehensive research to determine the optimal primary outcome measure for intervention trials in pediatric septic shock cases. Purpose: This study was aimed for an extensive investigation aimed at identifying the primary outcome measure for pediatric septic shock cases. Result: We compiled 17 articles from PubMed, Springer Nature, SAGE Pub, and Google Scholar. Ultimately, we included 5 articles that met the criteria. Conclusion: Collectively, these studies emphasize the multifaceted nature of childhood stunting, necessitating comprehensive strategies that encompass education, nutrition, and healthcare to combat its prevalence. The presented studies on pediatric sepsis management provide insights into tailored approaches, emphasizing lactate clearance, Shock Index (SI), Restricted Lactate Solution (RLS), and Hydrocortisone, Ascorbic Acid, and Thiamine (HAT) therapy as potential measures for improving patient outcomes. Despite limitations, these insights contribute to informed clinical decisions and advancements in pediatric sepsis management.